Ketogenic Diet for Epilepsy with Type 1 Diabetes - J Gordon Millichap (Pediatric Neurology Briefs, 2010)
Researchers at Medical University Vienna, Austria, report the efficacy and safety of the ketogenic diet (KD) in treatment of epilepsy in a 3-year 6 month-old girl with diabetes type 1 followed for 15 months.